Creating a Balanced, Symbiotic Relationship by Integrating Teaching & Research - Murnieks, A; Corey, J; Rinnert, G (Michigan Press, 2019)
As an educator, managing the numerous responsibilities of teaching, research, and service can be challenging. Relative to other disciplines, design educators are navigating a field where research is in its infancy. Adding to this complexity, faculty scholarly activity and research can involve a variety of trajectories, from practitioner-based work to traditional outlets of academic dissemination. With design education continually advancing, design pedagogy provides ample opportunity for the growth of research. Our conversation revolved around best practices for establishing a research agenda and linking it directly to the classroom. By creating a linear connection between research and teaching, faculty may enhance and broaden their research capabilities while creating innovative classroom activities, thus enhancing student learning.